EFFICIENCY STUDY OF MOORING TIME AND FISH LANDING AT PPI KAMBANG: STRATEGIES FOR OPTIMISATION PROCESS THROUGH GOVERNANCE - Octavia, Vanny Putri; Fatmawati, Riska; Brown, Arthur (Departemen PSP IPB, 2025)
Fish landing operations at Kambang Fishing Port are constrained by limited facilities, with only a single pier serving both docking and unloading activities. These constraints often result in prolonged landing times, especially during peak landing periods, when multiple vessels arrive in close succession. This study aims to analyze the relationship between fish landing time and mooring duration among trolling fishing vessels at PPI Kambang, West Sumatra, and to identify key factors influencing landing efficiency. A survey method was employed, involving the collection of primary data on mooring time, adequate unloading time, and idle time, supplemented by secondary data from port authorities. The results reveal that the efficiency of fish landing time ranges between 21.11% and 50.00%, with an average of 40.80%. The lowest efficiency was recorded on KM. Sepupu 02, while the highest was on KM. Melci 01 and KM. Wendri. Multiple linear regression analysis revealed strong correlations between landing efficiency and various factors, including vessel size, number of crew members, unloader age, total catch, and idle time. However, the regression model did not yield statistically significant results. These findings underscore the need for operational enhancements to minimize idle time and improve overall efficiency in fish landing processes. Key words: fish landing efficiency, fishing port, mooring time, trolling vessels, unloading process